PENGARUH PERBANKAN SYARIAH DAN MONETER SYARIAH TERHADAP INFLASI INDONESIA PERIODE 2004-2021 - Mulyadi, Sandi; Soleman, Riky; Imawan, Riswanda (Al-Hisab: Jurnal Ekonomi Syariah, 2022)
The problem of the pandemic and its impact on the health sector certainly has an impact on the economic sector which is also faced with an economic recession and one of the parts of the economy that is interesting to study is related to Indonesian inflation. Indonesia before and during the pandemic. Islamic banking uses DPK data and Islamic banking and monetary financing use SBIS and PUAS for Indonesia's inflation. The research method uses the Vector Correction Model (VECM) method using monthly time series data from 2004-2021. The results showed several findings, namely the long-term VECM test, the DPK, and PUAS variables had a positive effect, while the Islamic banking and SBIS financing variables had a negative effect on economic growth. In the future, inflation will stabilize against the shocks that occurred before and during the pandemic.